EUS-guided portal pressure gradient measurement with a simple novel device: a human pilot study - Jason B. Samarasena, MD; Jason Y. Huang, FRACP; Takeshi Tsujino, MD, PhD; Daniel Thieu, BSc; Allen Yu, BSc; Ke-Qin Hu, MD; John Lee, MD; Kenneth J. Chang, MD (VideoGIE, 2018)
Background and Aims: Portal hypertension is a serious adverse event of liver cirrhosis. Recently, we developed a simple novel technique for EUS-guided portal pressure gradient (PPG) measurement (PPGM). Our animal studies showed excellent correlation between EUS-PPGM and interventional radiology-acquired PPGM. In this video we demonstrate the results of the first human pilot study of EUS-PPGM in patients with liver disease. Methods: EUS-PPGM was performed by experienced endosonographers using a linear echoendoscope, a 25-gauge FNA needle, and a novel compact manometer. The portal vein and hepatic vein (or inferior vena cava) were targeted by use of a transgastric or transduodenal approach. Feasibility was defined as successful PPGM in each patient. Safety was based on adverse events captured in a postprocedural interview. Results: Twenty-eight patients underwent EUS-PPGM with 100% technical success and no adverse events. PPG ranged from 1.5 to 19 mm Hg and had excellent correlation with clinical parameters of portal hypertension, including the presence of varices (P = .0002), PH gastropathy (P = .007), and thrombocytopenia (P = .036). Conclusion: This novel technique of EUS-PPGM using a 25-gauge needle and compact manometer is feasible and appears safe. Given the availability of EUS and the simplicity of the manometry setup, EUS-guided PPG may represent a promising breakthrough for procuring indispensable information in the management of patients with liver disease.